Sparse Aperture Inverse Synthetic Aperture Radar Imaging for Maneuvering Targets With Migration Through Resolution Cells Correction - Jiaxing Yang; Yong Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Due to the nonstationarity of the echo, it is hard to form a well-focused sparse aperture inverse synthetic aperture radar (SA-ISAR) image for maneuvering targets by traditional algorithms. In this article, two algorithms are proposed to achieve the translational motion compensation and SA-ISAR imaging with migration through resolution cells (MTRC) correction for maneuvering targets respectively. First, with the stretch processing generated extra complex phase terms incorporated into the analysis, a modified parametric translational motion compensation algorithm is proposed to achieve the translational motion compensation. The translational parameters are estimated by optimizing the image entropy of the range–Doppler based ISAR image. Second, a novel SA-ISAR imaging framework with MTRC correction is proposed. After translational motion compensation, the nonstationary echo is intercepted by the short time window to extract the stationary echo. The missing data iterative adaptive approach-based random missing signal recovery and the interpolation-based MTRC correction are successively applied to the stationary echo. Subsequently, the iterative adaptive approach-based azimuth compression is applied in the framework to the valid MTRC-corrected range profile to form the focused ISAR image. Finally, the experimental results validate the effectiveness of the two proposed algorithms.